Gaming for Introducing Social Challenges and Responsibility to Young People - Perko, Igor; Mendiwelso-Bendek, Zoraida (Naše gospodarstvo/Our economy, 2018)
Gaming has the potential to support the development of young people’s capabilities in social responsibility (SR) and, at the same time, represents a threat of developing undesired behaviour patterns. Successful integration of gaming in the lives of young people requires a systemic approach, which, to the best of our knowledge, hasn’t been provided in the literature. We provide insight into this issue. In this paper, multiple methods are used. To elaborate the backgrounds on the gaming’s effects and social behaviour, the literature is analysed. To assess the state-of-the art of young people characteristics, their pressing social challenges and gaming evaluation reports are analysed. The synthesis is provided and placed in the context with social responsibility properties using system dynamics. Gaming concepts, appropriate for education for SR, and relationships between young people's challenges and the players in the gaming environment in SR terms are proposed. Currently, the loop of games development is negatively propelled by the short-term games demand. We propose effective feedback loops, linking young people and their social environment, using a SR tool set to provide demands to the game providers. The experience will support the games developers to design socially constructive games, aiming to develop the desired skills and competencies in social transformation processes of young people toward SR. The proposed model provides merely an overview model, designed by the literature review and state-of-the-art analysis. To fully understand the games’ effects on young people, a more detailed analysis is required.